2021
DOI: 10.2174/1871526520666200227102013
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effectiveness of a High Dose Versus the Standard Dose of Meropenem in Ventilator-associated Pneumonia Caused by Multidrugresistant Bacteria: A Randomized, Single-blind Clinical Trial

Abstract: Background: Meropenem standard doses are based on the minimum inhibitory concentration of sensitive pathogens and the pharmacokinetic parameter of not critically ill patients. We compared the efficacy of high versus standard dose of meropenem in ventilator-associated pneumonia (VAP). Methods: 24 out of 34 eligible patients were randomized to receive meropenem 3 g q8h (high dose group, 11 patients) or 2 g q8h (standard dose group, 13 patients) as a 3h infusion. Primary outcome was considered as clinical suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The other factor is that the current dose used in the ICU is not guided by the MIC of bacteria-resistant organisms ( 45 ). The initial 24 h–48 h of high-dose meropenem may be needed to overcome this subtherapeutic concentration in septic shock patients ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The other factor is that the current dose used in the ICU is not guided by the MIC of bacteria-resistant organisms ( 45 ). The initial 24 h–48 h of high-dose meropenem may be needed to overcome this subtherapeutic concentration in septic shock patients ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that the clinical success rate was similar between 2-g and 3-g doses over 3 hours infusion, but superiority in sequential organ failure assessment (SOFA) score reduction was found in the latter. 17 …”
Section: Discussionmentioning
confidence: 99%
“…The study demonstrated that the clinical success rate was similar between 2-g and 3-g doses over 3 hours infusion, but superiority in sequential organ failure assessment (SOFA) score reduction was found in the latter. 17 Various combination of bolus-extended infusion regimens were analyzed and simulated using pharmacokinetics modeling and simulation. Administration of meropenem 1.5-g or 2-g q6-8h preceded by once 0.5-g bolus could achieve and maintain 40% fT > 4 mg/mL until third day of treatment in compartmental analysis and simulation.…”
mentioning
confidence: 99%
“…CRP level and CPIS≥6 ratio are indicators of infection severity. [23][24][25] It is well known that the more severe the infection, the higher the risk of death. Therefore, it is reasonable that these two indicators were associated with the risk of death in the current study.…”
mentioning
confidence: 99%